General Anesthesia for an Infant With Pyloric Stenosis & Pierre Robin Sequence - Andrew J. Pittaway; Heather L. Naumann (Association of American Medical Colleges, 2012)
Abstract Introduction This problem-based learning (PBL) case contains an unusual association of two conditions. Specifically, it highlights the challenges inherent in safely anesthetizing an uncooperative infant with a potentially difficult airway and full stomach, and highlights the conflicting demands each complication places on the optimal anesthesia technique. This example encourages consideration of the clinical and practical anesthetic implications of two relatively uncommon conditions of early infancy in isolation, then to build upon this foundation by considering the impact that each has on the management of the other in the very rare instances where they may co-exist. Many of the principles so considered are generalizable to similar (but not identical) clinical dilemmas. Methods The material is presented as a narrative case history which poses several key questions crucial to the elucidation of optimal ongoing management. Each of these is expanded upon in the subsequent discussion along with included references and figures. Results This resource was originally presented as an abstract, and then as a PBL to faculty participants at a national pediatric anesthesia conference. It received uniformly enthusiastic evaluation from attendees and is worthy of a wider audience. Discussion The case is intended to stimulate group discussion and should complement relevant clinical experience and self-directed learning. It is primarily aimed at physician-trainees in a pediatric anesthesia fellowship program. The resource also provides an overview of the broader topics of anesthetic management of infantile pyloric stenosis and Pierre Robin sequence as well as current thinking about the optimal approach to managing general anesthesia in an infant so afflicted.